THINKING ABOUT RANDOM EVENTS FROM A LOGICAL POINT OF VIEW - Rosario D'Amico (Atti della Accademia Peloritana dei Pericolanti : Classe di Scienze Fisiche, Matematiche e Naturali, 2013)
The purpose of this essay is to identify a meaningful property of random events by using a theorem introduced in an unconventional symbolic language, which we shall call ℒu. More precisely, we attempt to show that every random event must occur at least once. The method, which we use, consists in defining, by means of sentences of the language ℒu, the concept of random event, after showing that some statements about the structural proprieties of the sentences of ℒu can be translated into sentences of the language ℒu itself. Thanks to this peculiar feature of ℒu, we achieve an important gain in facilitating the identification of the propriety looked for. In fact, it is easier to deal with sentences of a formal system, free of concealed assumptions and possibly misleading associations of meaning, than with true and false statements.